Microplastic Contamination in Groundwater Around Landfills: A Systematic Literature Review - Luthfia Aqilah Zahra; Mochamad Adhiraga Pratama; Sucipta Laksono (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Microplastic contamination in groundwater has become an emerging environmental concern, particularly in areas surrounding landfill sites. This study aims to systematically review the occurrence, distribution, characteristics, and influencing factors of microplastics in groundwater near landfills. A systematic literature review was conducted using the PRISMA 2020 framework, selecting articles published between 2021 and 2025 from Scopus and Google Scholar based on defined criteria. A total of 18 relevant studies were analyzed. The results show that microplastic abundance in groundwater varies widely, ranging from less than 1 particle/L to more than 1000 particles/L. Most microplastics are smaller than 500 µm, with polyethylene (PE) and polypropylene (PP) as the dominant polymers. Fragments and fibers are the most common forms, while color variation reflects differences in waste composition and environmental conditions. Microplastic distribution is influenced by distance from landfills, well type, depth, and age. Wells located within 1 km of landfills and shallow dug wells are more vulnerable to contamination. Landfill leachate plays a key role in transporting microplastics into groundwater systems. Therefore, integrated management strategies based on the Source–Pathway–Receptor approach are essential to mitigate contamination and protect groundwater quality.